2011
DOI: 10.2337/db10-0550
|View full text |Cite
|
Sign up to set email alerts
|

The Unconventional Role of Acid Sphingomyelinase in Regulation of Retinal Microangiopathy in Diabetic Human and Animal Models

Abstract: OBJECTIVEAcid sphingomyelinase (ASM) is an important early responder in inflammatory cytokine signaling. The role of ASM in retinal vascular inflammation and vessel loss associated with diabetic retinopathy is not known and represents the goal of this study.RESEARCH DESIGN AND METHODSProtein and gene expression profiles were determined by quantitative RT-PCR and Western blot. ASM activity was determined using Amplex Red sphingomyelinase assay. Caveolar lipid composition was analyzed by nano-electrospray ioniza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
100
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 83 publications
(107 citation statements)
references
References 41 publications
6
100
1
Order By: Relevance
“…1. We note that Cav-1 immunoreactivity is also prominent in retinal and choroidal vasculature, as expected, based on several reports of Cav-1 and caveolae in retinal vascular endothelium and pericytes (40,41,43,77,78). Both Müller glial (71) and RPE (72) cells play critical roles in maintaining the retinal environment by regulating active transport properties and blood-retinal barrier functions.…”
Section: Discussionsupporting
confidence: 90%
“…1. We note that Cav-1 immunoreactivity is also prominent in retinal and choroidal vasculature, as expected, based on several reports of Cav-1 and caveolae in retinal vascular endothelium and pericytes (40,41,43,77,78). Both Müller glial (71) and RPE (72) cells play critical roles in maintaining the retinal environment by regulating active transport properties and blood-retinal barrier functions.…”
Section: Discussionsupporting
confidence: 90%
“…33,34 Becker et al discovered that ceramide production in the lungs contributed to inflammatory cytokine production during cystic fibrosis, 35 and amitriptyline reduced ceramide production, inflammatory cytokine production, and inflammatory cell recruitment in a mouse model of cystic fibrosis. 35,36 Other studies have shown that SMase-mediated ceramide synthesis in plasma membranes promotes microvessel formation.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, DHA-rich diet fully prevents retinal vascular pathology, leading to a concomitant suppression of tissue inflammation and correction of EPC number and function. 97,98 Finally, endothelial cells not only are inert conduits delivering metabolites and oxygen but also establish a vascular niche that orchestrates regeneration and healing. Hence, a recent and elegant study uncovers that in response to liver injury, differential recruitment of proregenerative CXCR7-Id1 transcription factor versus profibrotic fibroblast growth factor 2 receptor type 1-CXCR4 angiocrine pathways balances regeneration and fibrosis.…”
Section: Future Directions and Conclusionmentioning
confidence: 99%